Rede Cegonha: maternal characteristics and perinatal outcomes related to prenatal consultations at intermediate risk - Franciele Aline Machado de Brito; Marcia Moroskoski; Bianca Machado Cruz Shibawaka; Rosana Rosseto de Oliveira; Beatriz Rosana de Oliveira Gonçalves Toso; Ieda Harumi Higarashi (SciELO, 2022)
Abstract Objective: to analyze the correlation between maternal characteristics and perinatal outcomes, with the number of prenatal consultations performed. Method: a cross-sectional study, carried out with 1,219 mothers and newborns stratified as intermediate risk according to the Programa Rede Mãe Paranaense, adaptation of the Rede Cegonha at the state level. Data were collected from the Birth Certificates. Spearman, Wilcoxon and Kruskal-Wallis tests were used to analyze the correlation between the variables of interest. Results: married women, with higher education, white and aged 30 years or older were the ones who most attended prenatal consultations. With regard to perinatal outcomes, children whose mothers had more frequent prenatal consultations had better Apgar and birth weight scores. High rates of cesarean delivery were identified before the onset of labor. Conclusion: maternal characteristics influence the process of adherence to prenatal care, impacting perinatal outcomes, indicating the relevance of these risk factors and the need to improve actions aimed at greater compliance with risk stratification and qualified and resolute care for pregnant women at intermediate risk.